Aging-related changes in protein and fat intake and their related meal types factors by longitudinal birth cohort analysis using the National Health and Nutrition Survey in Japan from 2001 to 2019 - Midori Ishikawa; Tetsuji Yokoyama; Osamu Hemmi (The Journal of Nutrition, Health and Aging, 2024)
Background: To provide seamless nutritional support from early adulthood to late adulthood in Japan, this study aimed to identify aging-related changes in protein and fat intake and meal types. Methods: Birth cohort analysis was conducted in this study. The protein intake, protein-to-energy ratio, fat intake, and fat-to-energy ratio in men and women from their 20s to 60s in 2001 was calculated using the data of the National Health and Nutrition Survey in Japan between 2001 and 2019 (n = 139,876, 47.0% men, mean age: 54.9 and 55.4 years for men and women, respectively). The intakes were calculated for every subsequent year, the aging-related changes were identified by age group, and the 99 food groups were classified into staple-focused meal types through factor analysis. The weighted average component value per 1 g of each food group was calculated, multiplied by the food weight, and totaled to determine the mean intake by meal type and to confirm the aging-related changes. The year when the slope changed before and after was identified through Joinpoint regression analysis. Results: The protein intake, protein-to-energy ratio, fat intake, and fat-to-energy ratio initially declined or remained unchanged with aging in almost all generations (20s to 60s in 2001) but began to increase after 8–15 years. The food groups were classified into rice, noodle, and bread types. The protein and fat intake from the noodle type initially showed a decreasing trend but began to increase with aging after 8–15 years in almost all generations in both sexes (p < 0.05 for difference in slope). Conclusions: The increase of protein intake and protein-to-energy ratio and fat intake and fat-to-energy ratio over time observed among Japanese adults may be related to the increased intake of food groups from noodle type meals. Thus, considering the type of staple food (i.e., rice, noodles, or bread) and its combination with other foods when adhering to a balanced diet is necessary.